Penilaian Diri Praktisi dan Akademisi Akuntansi atas Kemampuan di Bidang Teknologi Informasi - Harris, Lutfi (Jurnal Akuntansi Multiparadigma, 2010)
The International Federation of Accountants (IFAC) Education Committee issued IEPS 2, which state that information technology is pervasive in the world of business. Information technology can replace accountantâs role in financial statement preparation. Competence with this technology is imperative for professional accountant. The aim of this research is to examine accounting practitionerâs and educatorâs self IT perceived knowledge level, towards the important of PC knowledge, system design and development know-how, accounting package awareness, information technology auditing and language programming knowledgeÂ  for accountant professionals. Purposive sampling, hence, is employed to determine the number of respondents that will capable to represent public accountant practitioners, management accountant practitioners, public sector accountant practitioner and accountant scholar. Moreover, the respondent will be drawn within the universities and firms located at Jakarta. The data collected, hence will be analyzed using Mann-Whitney U test to examine the difference among practitioners towards academicians. It is shown by the standardize U statistics with 0,05 level of significant, eighteen item expressionâs scores are within acceptance region, confirm that there is no different perceived knowledge level among accountant scholar toward accountant professional.